Impact of Foreign Loan on Economic Growth of Pakistan: A Time Series Analysis - Saboor, Abdul; Yousaf, Shehzad; Narmeen, Naima; Fatima, Qandeel (Pakistan Journal of Humanities and Social Sciences, 2023)
This study examines effect of foreign loan on economic growth in Pakistan. The study uses time series data for the period of 1972-2022 and collects data from Economic Survey of Pakistan, SBP and WDI. ADF test results shows that variable inflation is stationary at level, while gross domestic product growth rate, foreign loan, and FDI are stationary at 1st difference. So, the study uses ARDL approach to detect the relationship between variables because integration order mixed. The ARDL model results shows that there is existence of long run relationship among all variables. The study results show that foreign loan has negative, FDI has positive, and inflation has negative effect on economic growth of Pakistan. This study recommends that Pakistan should overcome foreign loan and give friendly environment to foreign investors so that more and more FDI comes to country, that will help to improve economic growth of Pakistan.